Corporate Tax Avoidance, Earnings Management and Firm Value: The Moderating Role of ESG Ratings - Rivany Janete Eufrosina Fulianto; Vita Elisa Fitriana (Indonesian Journal of Accounting and Governance, 2025)
The topic related to firm value has persistently become a main issue among stakeholders, as it involves various factors. This study highly contributes in the literature for examining non-ethical factors involved in company, such as tax avoidance and earnings management. Hence, this study aims to analyze the effect of tax avoidance and earnings management on firm value by considering the role of Environmental, Social, and Governance (ESG) ratings as moderating variables. Further, the data was collected from 36 companies in the energy, property & real estate, basic materials, infrastructure, and manufacturing sub-sectors listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The moderated regression analysis was utilized to analyze the data. Surprisingly, neither tax avoidance nor earnings management has a significant impact on company value. However, ESG ratings have a significant negative impact on company value. It indicates that the stakeholders might not be considering ESG as a value-adding factor. Furthermore, ESG was unable to moderate the relationship both tax avoidance and earnings management towards company value. These findings suggest that the integration of ESG still requires broader understanding and acceptance in the Indonesian capital market, as well as the need for a strategic approach in ESG implementation to positively impact firm value.